Naked exclusion under exclusive-offer competition - Hiroshi Kitamura; Noriaki Matsushima; Misato Sato; Wataru Tamura (Osaka University, Institute of Social and Economic Research (ISER), 2025)
This study constructs a model of exclusive-offer competition between two existing up-stream firms. Under exclusive-offer competition, the upstream firm's profit depends on the rival's exclusive offer. If the rival makes an exclusive offer acceptable for the downstream firm, the upstream firm is excluded unless it succeeds in exclusion. Consequently, the upper bound of exclusive offers becomes higher than when one of the upstream firms is a potential entrant that cannot make any exclusive offer. Thus, the exclusion of the existing upstream firm can be an equilibrium outcome even in the case where the potential entrant is never excluded.
Keywords: L12; L41; L42; 330; Exclusive dealing; Exclusive-offer competition; Imperfect competition; Antitrust policy